2020
DOI: 10.1029/2019je006077
|View full text |Cite
|
Sign up to set email alerts
|

Orbit‐Spin Coupling and the Triggering of the Martian Planet‐Encircling Dust Storm of 2018

Abstract: The Martian global dust storm (GDS) of 2018 began soon after the southern spring equinox, which is quite early in the dust storm season. The origins of early‐season GDS, including those of 1977, 2001, and now 2018, have been mysterious, as atmospheric dynamical investigations and numerical modeling experiments have been unable to explain or reproduce the timing of these events. We employ a newly expanded catalog of historic Martian GDS for our investigation, which includes 2018 and the telescopically observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
(143 reference statements)
0
10
1
Order By: Relevance
“…GCMs initialized with a finite supply of surface dust show source regions will be depleted quickly and inhibit dust storm activity (Kahre et al, 2005;Mulholland et al, 2013;Newman & Richardson, 2015). This is inconsistent with multidecadal observations (Shirley et al, 2020;. Kahre et al (2005) concluded that source regions are large reservoirs, providing dust for lifting on at least multidecadal timescales, and that the interannual variability in dust storms is not due to the availability of surface dust.…”
mentioning
confidence: 97%
“…GCMs initialized with a finite supply of surface dust show source regions will be depleted quickly and inhibit dust storm activity (Kahre et al, 2005;Mulholland et al, 2013;Newman & Richardson, 2015). This is inconsistent with multidecadal observations (Shirley et al, 2020;. Kahre et al (2005) concluded that source regions are large reservoirs, providing dust for lifting on at least multidecadal timescales, and that the interannual variability in dust storms is not due to the availability of surface dust.…”
mentioning
confidence: 97%
“…Specifically, short‐term orbital forcings also need to be analyzed in the frame of the modeled feedbacks of the Earth system, such as fast‐slow responses of dynamical systems (see e.g., Seshadri, 2017). In addition, other unexpected mechanisms involving orbital changes and internal climate dynamics could be operating on the Earth, as in the case of planet Mars, where the orbital dynamics of this planet has been linked to large‐scale atmospheric circulation patterns; indeed, a weak spin‐orbit coupling between the orbital and rotational angular momenta of Mars has been argued to possibly explain its remarkable dust storms (Newman et al., 2019; Shirley et al., 2020). In our opinion, regardless of the amplitudes of the forcing involved, one of the most promising mechanisms called upon to explain the bases of these complex mechanisms behind the interactions among these orbital oscillations and the Earth system will be through the Kuramoto models of synchronization, assuming that their components are under non‐linear couplings.…”
Section: Discussionmentioning
confidence: 99%
“…The strengthened Hadley circulation lofted dust to very high altitudes, ∼70 km, and led to almost anvil‐cloud‐like distributions of dust in the middle and upper atmosphere. Additionally, this seasonally atypically strong Hadley circulation produced dynamical heating of mid‐altitude air at high latitudes in both hemispheres due to adiabatic warming in the descending branches of the equinoctial circulation (Shirley et al., 2020b). Indeed, both observations (Kass et al., 2019) and modeling (e.g., Bertrand et al.…”
Section: Storm Evolution and Timelinementioning
confidence: 99%